The WTO law of subsidies a comprehensive approach - Bénitah, Marc (Wolters Kluwer Kluwer Law International, 2019)
The WTO Law of Subsidies' provides a comprehensive analysis of the law of subsidies under the WTO regime. Subsidies are arguably the dominant theme in International Economic Law and a prolific case law has been elaborated by WTO Panels and Appellate Body in response to the multitude of complaints lodged in the past two decades (Softwood Lumber, Airbus, Boeing, etc.). The case law and norms disciplining subsidies under the WTO legal regime are of utmost importance first for international trade ministries, parliaments, and international institutions (OECD, CNUCED, FAO, etc.). However, non-governmental organizations (World Wide Fund, etc.) are also directly concerned by this topic regarding, for example, fisheries subsidies and their impact on overexploitation of marine resources. The private sector (fishing fleets, fishermen, extractive industries, etc.) is also affected by this topic particularly regarding future investments.